El uso de las tics en el proceso de enseñanza aprendizaje en el área de estudios sociales en los alumnos del octavo año de educación básica del colegio técnico Santa Rosa, del cantón santa Rosa, año lectivo 2012-2013 - Bazarán Robles, Cristian Manuel (2013)
I is important to emphasize that the investigative process developed at the school under study, let me get to find that the teachers in the area of ​​social studies 8th grade basic education do not apply the technologies of information and communication tics in the process teaching and learning.